Effect of gum arabic concentrations on drying kinetics, anthocyanin degradation and product qualities of purple rice bran extract dried by foam-mat technique - L.T.K. Loan; B.T. Vinh; N.V. Tai (My University, 2023)
Derivation and application of
Keywords: Gum arabic; Degradation; Food Quality and Safety Studies